From Report to Mythus. Jiří Kolář’s Plays as Creative Transformation of the Shoah Testimonies - Firlej, Agata (Poznańskie Studia Slawistyczne, 2017)
Kolář’s plays Chléb náš vezdejší and Mor v Athénách, written at the turn of the fifties and the sixties, are the examples of aestheticization of testimonies and other texts about the Shoah. Kolář’s creative path is in a way pars pro toto of artistic and literary search of many authors reacting to the experience of Shoah and to many texts describing this hecatomb. Doubt in the previous aesthetics and in the polyphonic load of words is one of the most common experiences in the second half of the 20th century – until now. The author activates memory or cultural connotations of receiver and by eliminating a factual layer that could became a psychological safety valve that distracts, focuses a viewer (reader) on the most important and by it the most difficult to bear: to the event itself.